Novel MTTP Gene Mutation in a Case of Abetalipoproteinemia with Central Hypothyroidism - Pembe Soylu Ustkoyuncu; Songül Gokay; Esra Eren; Durmus Dogan; Gokce Yıldız; Aysegul Yılmaz; Fatma Turkan Mutlu (Galenos Yayincilik, 2020)
Abetalipoproteinaemia (ABL) is an autosomal recessive disorder characterized by very low plasma concentrations of total cholesterol and triglyceride (TG). It results from mutations in the gene encoding microsomal TG transfer protein (MTTP). A nine-month-old girl was admitted to hospital because of fever, cough, diarrhea and failure to thrive. She had low cholesterol and TG levels according to her age. The peripheral blood smear revealed acanthocytosis. Thyroid function test showed central hypothyroidism. Cranial magnetic resonance imaging revealed the retardation of myelination and pituitary gland height was 1.7 mm. A homozygous novel mutation [c.506A>T (p.D169V)] was detected in the MTTP gene. Vitamins A, D, E, and K and levothyroxine were started. The coexistence of ABL and central hypothyroidism has not previously been reported. A homozygous novel mutation [c.506A>T (p.D169V)] was detected in the MTTP gene.